2010
DOI: 10.2169/internalmedicine.49.3373
|View full text |Cite
|
Sign up to set email alerts
|

Hypoglycemic Coma in a Patient with Anorexia Nervosa Coincident with Acute Exacerbation of Liver Injury Induced by Oral Intake of Nutrients

Abstract: A 33-year-old woman with anorexia nervosa was admitted because of severe malnutrition. Acute liver injury was observed soon after the beginning of oral intake. She was prohibited from eating for 10 days and treated with parenteral nutrition until liver dysfunction was improved. One week after resuming oral intake, she presented severe hypoglycemic coma along with acute exacerbation of hepatocytic injury. Clinical laboratory data suggest that insufficient gluconeogenesis in acute liver injury was involved in se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
26
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 14 publications
1
26
2
Order By: Relevance
“…However, the development of elevated liver enzymes during refeeding often becomes a clinical issue during the therapeutic process. Although rare, there are reports of patients with AN who developed marked fatty liver accumulation, leading to fatal hepatic failure [3], or who developed liver injury with hypoglycemic coma during refeeding [4]. …”
Section: Introductionmentioning
confidence: 99%
“…However, the development of elevated liver enzymes during refeeding often becomes a clinical issue during the therapeutic process. Although rare, there are reports of patients with AN who developed marked fatty liver accumulation, leading to fatal hepatic failure [3], or who developed liver injury with hypoglycemic coma during refeeding [4]. …”
Section: Introductionmentioning
confidence: 99%
“…In contrast, in a few reports authors have found elevations in liver tests during the process of refeeding. 4,7 In the largest study to date (n = 126), 96% of patients had normalizing aminotransferases by 4 weeks of enteral nutrition, whereas only 4% had worsening with refeeding. 11 Therefore, the objective of this study was to analyze, in a large sample of adolescents with AN hospitalized in a tertiary children's hospital, the prevalence of elevated liver enzymes, predictors of elevated liver enzymes including degree of malnutrition and refeeding, and the evolution of elevated liver enzymes throughout the hospitalization.…”
mentioning
confidence: 99%
“…4 Liver enzyme abnormalities among patients with AN remain poorly characterized. The few studies of elevations in alanine aminotransferase (ALT) and aspartate aminotransferase (AST) levels in AN are limited to case reports [4][5][6][7][8][9][10] and studies with small sample sizes, [11][12][13][14][15] with a wide range in the reported prevalence of elevated ALT/AST, from 0% to 76%. 11 In initial studies researchers found that elevated ALT/AST was associated with lower body mass index (BMI) 11,13 and decreased percentage body fat.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…It has been suggested that hypoglycemia associated with anorexia nervosa is a serious risk factor, especially when body weight falls below 30 kg, but in men it may occur at a higher total body weight 4951. Sudden death related to hypoglycemia has been reported in ED patients, usually associated with other complications, such as pulmonary edema, cerebral hemorrhage (Weber’s syndrome) or coincident with acute exacerbation of liver injury induced by oral intake of nutrients 5254…”
Section: Resultsmentioning
confidence: 99%